Analisis Sosial Ekonomi dalam Pemanfaatan Fasilitas Kesehatan untuk Berobat Jalan di Provinsi Jawa Barat : Analisis Data Susenas Tahun 2017 - Fairuz Rabbaniyah; Mardiati Nadjib (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
In 2008-2014 the utilization of health facilities for medical treatment in Indonesia has decreased. Accordingto BPS data, in 2008 the utilization of health facilities for outpatient treatment was 33.4%, in 2012 it was 30%and in 2014 it was 27.1%. The purpose of this study was to determine the socio-economic factors that influencethe utilization of health facilities for outpatient treatment in West Java Province. This study uses secondary data,namely data from the National Socio-Economic Survey (Susenas) in 2017. The research respondents were 22,955heads of households in West Java Province. The method used in this study uses the econometric approach using theBinary Regression method, namely the logit model and probit model. The results of this study found that incomefactors and employment status of household heads positively influence the views of coefficient values. The incomeand employment status of the head of the household significantly influence the utilization of health facilities. Thevalue of p-value for income is 0.001 (p-value <0.05), while the p-value for employment status is 0.08 (p-value<0.1). Socio-economic factors that influence the utilization of health facilities in West Java Province are incomeand employment status of the head of the household.